A Histomorphological Pattern Analysis of Pulmonary Tuberculosis in Lung Autopsy and Surgically Resected Specimens. (21st March 2016) - Gupta, Mamta; Lobo, Flora D.; Adiga, Deepa Sowkur Anandarama; Gupta, Abhishek
Abstract : Background . Tuberculosis (TB) is a major cause of morbidity and mortality globally. Many cases are diagnosed on autopsy and a subset of patients may require surgical intervention either due to the complication or sequelae of TB. Materials and Methods . 40 cases of resected lung specimens following surgery or autopsy in which a diagnosis of pulmonary tuberculosis was made were included. Histopathological pattern analysis of pulmonary tuberculosis along with associated nonneoplastic changes and identification of Mycobacterium tuberculosis bacilli was done. Results . The mean age of diagnosis was 41 years with male predominance (92.5%). Tuberculosis was suspected in only 12.1% of cases before death. Seven cases were operated upon due to associated complications or suspicion of malignancy. Tubercular consolidation was the most frequent pattern followed by miliary tuberculosis. The presence of necrotizing granulomas was seen in 33 cases (82.5%). Acid fast bacilli were seen in 57.5% cases on Ziehl-Neelsen stain. Conclusion . Histopathology remains one of the most important methods for diagnosing tuberculosis, especially in TB prevalent areas. It should be considered in the differential diagnosis of all respiratory diseases because of its varied clinical presentations and manifestations.